Age as a prognostic factor of 30-day mortality in hemorrhagic stroke patients: A Thai large tertiary care referral center - Wilaiwan Chongruksut (2020)
© 2020 Objective: The aim of the present study was to identify incidences and prognostic factors for 30-day mortality of hemorrhagic strokes (HS) and divide them into intracerebral hemorrhage (ICH) and subarachnoid hemorrhage (SAH). Methods: This retrospective cohort study was conducted using medical records of patients who underwent surgery due to HS, between January 2013 and April 2017, at Chiang Mai University Hospital, a large tertiary referral center, in Northern Thailand. 30-day mortality was followed after surgery. Prognostic factors included patients' characteristics, and clinical date related to early death, were determined. Data analysis was performed using Cox's proportional hazards model. Results: 460 patients were enrolled. The 30-day mortality rate was 8.8% and 12.3%, in ICH and SAH patients, respectively. Multivariable analyses demonstrated that the prognostic factors of early mortality in ICH patients were age 65–70 years (Adjusted HR 3.10 (95%CI 1.14–8.41)), >70 years (Adj.HR 2.64 (95%CI 1.09–6.36)) and hypertension (HT) (Adj.HR 2.98 (95%CI 1.25–7.12)). In SAH patients, prognostic factors were HT (Adj.HR 7.32 (95%CI 2.12–25.29)), and atrial fibrillation (AF) (Adj.HR 5.48 (95% CI 1.57–19.09)). Conclusions: Ages over 65 years and HT were an important predictor of 30-day mortality in a subgroup of ICH patients, whereas HT and AF were significant prognostic factors in SAH. To reduce early death, management for stroke cases needed to take into account the specifics for older age patients with HT, and AF.